Louise Michel - Maclellan, Nic (Melbourne/ New York : Ocean Press, 2004)
Louise Michel was the incendiary leader of the 1871 Paris Commune, when the city's population rose up to establish a short-lived workers government. An anarchist and an irrepressible rebel, "The Red Virgin" spent much of her life on the run, in exile, in jail, or in danger of being locked away in mental asylums. This is Michel's defiant story, with commentaries by Emma Goldman, Bertolt Brecht, Sheila Rowbotham, Howard Zinn, Victor Hugo and Karl Marx
Keywords: Michel, Louise, -- 1830-1905.